2021
DOI: 10.1073/pnas.2004840117
|View full text |Cite
|
Sign up to set email alerts
|

Toward the correction of muscular dystrophy by gene editing

Abstract: Recent advances in gene editing technologies are enabling the potential correction of devastating monogenic disorders through elimination of underlying genetic mutations. Duchenne muscular dystrophy (DMD) is an especially severe genetic disorder caused by mutations in the gene encoding dystrophin, a membrane-associated protein required for maintenance of muscle structure and function. Patients with DMD succumb to loss of mobility early in life, culminating in premature death from cardiac and respiratory failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 82 publications
(90 reference statements)
0
50
0
Order By: Relevance
“…(dystriphin-targeted therapies), such as adeno-associated virus (AAV)-mediated micro/minidystrophin gene delivery, synthetic antisense oligonucleotides for exon skipping, nonsense readthrough, CRISPR-Cas9 (clustered regularly interspaced short palindromic repeat-CRISPR-associated protein 9)-mediated genome editing, protein replacement therapies, and primarily utropin; (2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63]. However, it has been reported that clinical trials with this strategy have to be discontinued because of off-target effects that cause chromosomal abnormalities.…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
“…(dystriphin-targeted therapies), such as adeno-associated virus (AAV)-mediated micro/minidystrophin gene delivery, synthetic antisense oligonucleotides for exon skipping, nonsense readthrough, CRISPR-Cas9 (clustered regularly interspaced short palindromic repeat-CRISPR-associated protein 9)-mediated genome editing, protein replacement therapies, and primarily utropin; (2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63]. However, it has been reported that clinical trials with this strategy have to be discontinued because of off-target effects that cause chromosomal abnormalities.…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
“…The N and C termini are essential to maintain proper dystrophin function and membrane integrity. However, the central rod domain contains redundant repeats and thus can be shortened while still maintaining functionality [6]. Such internally truncated forms of dystrophin may be expressed in BMD patients, thereby providing evidence that skipping the associated exons is a promising treatment strategy for DMD patients [13].…”
Section: Dystrophin Structurementioning
confidence: 99%
“…Another challenge associated with AAV-mediated delivery is the risk of AAV integration into DNA DSB sites [104]. Finally, AAV vectors may accumulate in the liver, posing the risk of deleterious side effects or dose-dependent toxicity [6].…”
Section: Deliverymentioning
confidence: 99%
See 2 more Smart Citations